RETML-4: Advancements in esophageal cancer surgery with four-arm robotic thoracic esophagectomy with total mediastinal lymphadenectomy - Xuefeng Leng; Koshiro Ishiyama; Hiroyuki Daiko (Intelligent Surgery)
Surgery remains a primary treatment for esophageal cancer. As the field has progressed from open esophagectomy (OE) to minimally invasive esophagectomy (MIE) and further to robot-assisted minimally invasive esophagectomy (RAMIE), not only has the surgeon's understanding and perception of the disease deepened, but the advancements in operative techniques have also led to improved post-operative recovery and oncological outcomes for patients. The esophageal surgery team at the National Cancer Center Hospital has elevated RAMIE to a new theoretical and practical level with their technique: esophageal cancer surgery with four-arm robotic esophagectomy with total mediastinal lymphadenectomy (RETML-4), rooted in the robotically enhanced surgical anatomy (RESA) philosophy. This article provides a comprehensive overview of the conceptual foundation and operative process of this innovative surgical approach.